THE COMPLIANCE TREATMENT OF A PULMONARY TUBERCULOSIS PATIENTS AT TRIENGGADENG COMMUNITY HEALTH CENTER REGENCY OF PIDIE JAYA - Fauziah Andika; Marniati Marniati (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Pulmonary Tuberculosis (TB) is still a public health problem in the world. Not only in the world, in Indonesia is also a public health problem both in terms of mortality, the incidence of the disease and its diagnosis and treatment. A lot of factors affect whether a person is obedient and submissive in treatment of pulmonary TB disease, which are due to the role of health workers, the role of the PMO (supervisors of taking medicine), distance and knowledge of the patient. Pulmonary tuberculosis patients must be able to do the treatment on an ongoing basis, where the treatment is done for 6 months without stopping. Noncompliance treatment of pulmonary tuberculosis patients can increase the number of smear-positive pulmonary tuberculosis patients. Keywords: Compliance treatment, age, distance, PMO's role and the role of health workers